2022
DOI: 10.1094/pdis-07-21-1364-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Stalk Rot of Celery Caused by Erwinia rhapontici in China

Abstract: Species belonging to the genus Erwinia cause diseases in many economically important plants (Mansfield et al. 2012). In May 2021, celery plants (Apium graveolens var. dulce) showing soft rot symptoms were observed in greenhouses (cv. Queen of France) in Boye County, Baoding, Hebei Province (North China). Disease symptoms began with pinkish water-soaked lesions on the midrib of celery stalks, but at the same time the leaves and root did not show symptoms. The infected celery plants rapidly developed brownish ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Manual review of records added to the DDB in 2021 highlight one first report on a new host plant. Wang et al (2022) reported the first instance of E. rhapontici causing stalk rot of celery in China. According to the authors this is the first time E. rhapontici has been reported on this host plant.…”
Section: Erwinia Rhaponticimentioning
confidence: 99%
See 1 more Smart Citation
“…Manual review of records added to the DDB in 2021 highlight one first report on a new host plant. Wang et al (2022) reported the first instance of E. rhapontici causing stalk rot of celery in China. According to the authors this is the first time E. rhapontici has been reported on this host plant.…”
Section: Erwinia Rhaponticimentioning
confidence: 99%
“…Soft rot symptoms were observed on celery in May 2021 in Hebei Province. Wang et al (2022) emphasise the threat this poses to local celery production and the need for prevention and control measures to manage it. This is not the first occurrence of E. rhapontici in China overall.…”
Section: Erwinia Rhaponticimentioning
confidence: 99%